"A Body Without a Head". The Elite of the Muslim Minority in the Bulgarian Lands at the Turn of the 20th Century - Popek, Krzysztof (Balcanica Posnaniensia. Acta et studia, 2019)
The Russo-Turkish War of 1877–1878 led to the end of the Ottoman rule in the Bulgarian lands, which entailed a huge emigration of the Muslim population. The Ottoman elite was the first who decided to leave. Officials, hodjas, imams, officers, landowners, urban dwellers, and the intelligentsia moved to the Ottoman Empire out of fear of retaliation for having links with the former authorities. Additionally, after the Unification of the Principality of Bulgaria and Eastern Rumelia in 1885, there was a new migration wave of Muslim officials, local activists, and militia officers from Southern Bulgaria. As a result, in 1879–1949 about 80% of the Muslim population of Bulgaria were small farmers, about 19% lived in cities as craftsmen, and only about 1% had a chance to make a career as entrepreneurs or merchants. The paper will focus on the three elite groups who correspond with the traditional division of the elite: the political (muftis), the economic (landowners, merchants, entrepreneurs), and the intellectuals (teachers – hodjas).